Al-Qiyam Al-Islamiyyah and its impact on Muslim communities' stability - Ahmed Mohamed, Ismaiel Hassanein; Idrus, Faizah; Mohammed Rawash, Fouad Mahmoud (IIUM PRESS, 2017)
Al-Qiyqmia is an Arabic term that means Values. The term: Qiyam is a plural of Qimah which means value. It addresses every aspect of a Muslim’s life, from greetings to international relations. It is universal in its scope and in its applicability. The distinction between human beings over other creatures is that human behaviour is controlled or limited by certain ethical values (qiyam) which purify their soul. These qiyam are reliable benchmarks to measure the individual’s and societies’ behaviour, especially those who are enjoying Islamic ethics. Thus, the authorities running educational institutions and training centers are bound to teach the Islamic Qiyam to motivate tolerance, justice and equity among the Muslims. The objective of this paper is to explore the role of Islamic qiyam in protection human behaviours, its implications on the consolidation of unity among Muslim societies with diverse culture, and participation of educational institutions in instilling these qiyam among individuals, which eventually leads to the development of Muslim Nations; educationally, culturally, scientifically, economically and politically, etc.The paper is based on a descriptive and analytical method, since it describes the qiyam suggested by the Holy Qur’an and the Sunnah, and to analyses the prevailing ethical problems among the Muslims, and how it could be resolved. The paper is intended to identify the most important values (qiyam) to be taught by various educational or training institutions in Islamic countries to serve as a comprehensive unifying framework for the Muslim Ummah.